Clinical Holistic Medicine (Mindful,Short-Term Psychodynamic Psychotherapy Complemented with Bodywork) in the Treatment of Experienced Mental Illness - Søren Ventegodt; Suzette Thegler; Tove Andreasen; Flemming Struve; Lars Enevoldsen; Laila Bassaine; Margrethe Torp; Joav Merrick (The Scientific World Journal)
Short-term psychodynamic psychotherapy (STPP) complemented with bodywork improved 31 of 54 patients (57.4%, 95% CI: 43.21–70.77%) who rated themselves mentally ill before treatment. Calculated from this we find 1.41 < NNT < 2.31; we estimate NNH > 500. Of the 54 patients, 40% had already had traditional treatment that did not help them. Bodywork helped the patients to confront repressed painful feelings from childhood and this seemingly accelerated and improved the therapy. The patients received in average 20 sessions over 14 months at a cost of 1600 EURO. For the treatment responders, all measured aspects of life (on a five point Likert Scale) improved significantly, simultaneously, and radically: somatic health (from 2.9 to 2.3), self-esteem/relationship to self (from 3.5 to 2.3), relationship to partner (from 4.7 to 2.9 [no partner was rated as “6”]), relationship to friends (from 2.5 to 2.0), ability to love (from 3.8 to 2.4), self-assessed sexual ability (from 3.5 to 2.4), self-assessed social ability (from 3.2 to 2.1), self-assessed working ability (from 3.3 to 2.4), and self-assessed quality of life (from 4.0 to 2.3. Quality of life as measured with QOL5 improved (from 3.6 to 2.3 on a scale from 1 to 5; p < 0.001). This general improvement strongly indicated that the patient had healed existentially, i.e., had experienced what Aaron Antonovsky (1923–1994) called “salutogenesis”, defined as the process exactly the opposite of pathogenesis. For the treatment responders, the treatment provided lasting benefits, without the negative side effects of drugs. A lasting, positive effect might also prevent many different types of problems in the future.